The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/bios11080244
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Artificial Olfaction Systems with a Focus on Surface Plasmon Resonance for the Analysis of Volatile Organic Compounds

Abstract: The last three decades have witnessed an increasing demand for novel analytical tools for the analysis of gases including odorants and volatile organic compounds (VOCs) in various domains. Traditional techniques such as gas chromatography coupled with mass spectrometry, although very efficient, present several drawbacks. Such a context has incited the research and industrial communities to work on the development of alternative technologies such as artificial olfaction systems, including gas sensors, olfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 226 publications
0
19
0
1
Order By: Relevance
“…and anthropogenic (fossil fuels, automobile exhaust, etc.) [ 24 ]. Studies have shown that most VOCs have adverse effects on human health, causing symptoms such as headaches, and nose, eye and throat irritation [ 25 ].…”
Section: Advances In Electrochemical Signal Amplification Strategies ...mentioning
confidence: 99%
See 1 more Smart Citation
“…and anthropogenic (fossil fuels, automobile exhaust, etc.) [ 24 ]. Studies have shown that most VOCs have adverse effects on human health, causing symptoms such as headaches, and nose, eye and throat irritation [ 25 ].…”
Section: Advances In Electrochemical Signal Amplification Strategies ...mentioning
confidence: 99%
“…In addition, VOC and odor analysis can be used for quality assessment in the food, beverage, and flavor industries. Therefore, it is crucial to monitor the nature and concentration of these compounds in indoor or outdoor environments [ 24 ].…”
Section: Advances In Electrochemical Signal Amplification Strategies ...mentioning
confidence: 99%
“…In the past decades the literature has reported novel VOC sensors and biosensors designed for solving these issues with remarkable results, as reported in different reviews and research papers [ 53 , 54 , 55 , 56 , 57 ]. In general, VOC sensors are devices capable of registering electrical, photophysical, mechanical, or biological changes, after the interaction with specific volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, elastic sensitivity has been presented as a novel way to measure gases by a small shift in elastic properties of nanostructured layers [ 11 , 20 , 21 , 22 , 23 ]. Several studies to achieve sensors based on nanostructured sensitive layers had been performed [ 24 , 25 , 26 ], resulting in highly sensitive and selective sensors to improve electronic nose technology for detecting, discriminating and classifying target gases. For example, Bhasker et al [ 27 ] conclude that both mass loading and change in elasticity, are the sensing mechanisms in ammonia detection.…”
Section: Introductionmentioning
confidence: 99%